(untitled) (Ozone Therapy Global Journal, 2012)
To the editor: We read with great interest the manuscript entitled: “Oxygen-Ozone Therapy is at a Cross-Road” Rev. Esp. Ozono. 1(1):74-86.1 First, we noted that some of the criteria considered by the authors do not appear to fit with reality. In the section: A few of the present methodologies are of doubtful value and may be dangerous or ineffective it is mentioned that the reason why Cubans do not use major autoemotherapy is because: “[…] every day they have to treat thousands of patients, it appears impossible to perform M-O3-AHT for lack of time and money”.